ANALYSIS OF PATHOGENIC GENE MARKER hlyF IN ESCHERICHIA COLI CAUSES OF COLLIBACILLOSIS IN FREE-RANGE CHICKEN - Chandrawan, I Gede Eka; Mahardika, Gusti Ngurah Kade; Besung, I Nengah Kerta; Suarjana, I Gusti Ketut (Buletin Veteriner Udayana, 2022)
Colibacillosis by Avian Pathogenic Escherchia coli (APEC) is an infectious disease in poultry. The ability of APEC to cause disease depends on various virulence factors, including hlyF . The study aimed to prove the existence of the APEC hlyF gene in Bali and to find out the DNA sequences of these hlyF genes and their kinship with the hlyF gene from other countries. This study used two APEC isolates from free range chicken in Tabanan and Badung regencies. The isolates have been purified and were available at the Bacteriology Laboratory of Veterinary Medicine Faculty, Udayana University. DNA isolates were isolated using Chelex 10%. The hlyF gene is amplified using published DNA primers by polymerase chain reaction (PCR). PCR products were sequenced at First Base Laboratories in Malaysia using the Sanger’s Dideoxy Nucleotide Termination method. Both the hlyF gene sequences that can be analyzed have 100% homology with a readable length of 518 bp. Phylogenic test with 25 DNA sequences of hlyF gene on Escherichia coli and other bacteria in the world using UPGMA method with bootstrap (500 repetitions) was conducted with MEGA 5.2. All data have six polymorphic sites of nucleic acid and two polymorphic sites of amino acid . The hlyF gene from Bali was in same group with hlyF genes from various countries in the world. This gene can be used as a pathogenic marker of APEC in Indonesia.